Technical Graphics Communication - L. Miller Craig (MC Graw Hill, 2003)
In its third edition, Technical Graphics Communication,, has become a standard in the field of engineering and technical graphics. This text presents both traditional and modern approaches to technical graphics, providing engineering and technology students with a strong foundation in standard drafting practices and techniques.